Six steps to songwriting success : the comprehensive guide to writing and marketing hit songs - Blume, Jason (New York Billboard Books, 2004)
What's the secret to writing a hit song? It's as simple as 1-2-3-4-5-6! Innovative, practical, and inspiring, Six Steps to Songwriting Success presents a surefire step-by-step approach to mastering the elements consistently found in hit songs. Author Jason Blume, a songwriter with the rare distinction of having had songs on the Country, Pop, and R & B charts simultaneously, has packed this book with such key aids as the three-step lyric writing technique used by the pros; lyric, melody, and demo checklists; and tools for self-evaluation-plus many other exercises that work. Blume's warm, humorous.
Keywords: Composición -- Música; Creatividad